Functional Profiling of Beneficial Soil Microbes Improving Plant Stress Tolerance: Mechanisms, Applications, and Public Health Implications - Lahar Jyoti Bordoloi; Sindhuja suram; Abhijit Debnath; Ratan Das (Public Health, 2026)
Plant stress caused by abiotic and biotic factors poses a significant threat to global agricultural productivity and food security. Beneficial soil microorganisms, particularly plant growth-promoting rhizobacteria (PGPR), mycorrhizal fungi, and endophytic microbes, play a critical role in enhancing plant stress tolerance through diverse functional mechanisms. This review provides a comprehensive analysis of the functional profiling of beneficial soil microbes and their contributions to improving plant resilience under stress conditions such as drought, salinity, temperature extremes, and pathogen attack. Key mechanisms include phytohormone modulation, osmolyte accumulation, antioxidant enzyme activation, induced systemic resistance, and nutrient acquisition enhancement. Advances in omics technologies, including metagenomics, transcriptomics, and metabolomics, have facilitated deeper insights into microbial functions and plant–microbe interactions. Emerging approaches such as microbiome engineering, biofertilizer development, and precision agriculture are discussed for their potential to mitigate stress impacts sustainably. Furthermore, the implications of microbial-based stress management strategies for environmental sustainability and public health are highlighted, particularly in reducing agrochemical use and improving food quality. Despite promising developments, challenges related to field variability, microbial survival, and large-scale application remain. Future research directions emphasize the integration of multi-disciplinary approaches to optimize microbial interventions for sustainable agriculture and global health